Improving Mechanical Performance of Hybrid Polymer Composites: Incorporating Banana Stem Leaf and Jute Fibers with Tamarind Shell Powder - Karuppusamy Manickaraj; Aruchamy Karthik; Sivasubramanian Palanisamy; Manivannan Jayamani; Syed Kashif Ali; Subramanian Lakshmi Sankar; Saleh A. Al-Farraj (BioResources)
Mechanical properties were evaluated for bio-natural fiber-reinforced epoxy hybrid composites made with varying amounts of jute, banana stem leaves (BSL), and tamarind shell powder (TSP). Each composite design had varying weight percentages of jute and BSL (5 to 25%) and a consistent mix of TSP (10%) and epoxy resin (60%). The tensile strength, flexural strength, interlaminar shear strength (ILSS), impact strength, hardness, and water absorption were examined. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used to investigate chemical bonding and morphology. The findings indicated a relationship between fiber and filler content and mechanical properties of composites, with 20% jute fiber content resulting in the highest performance. The tensile strength of the composite increased by 24.6%, rising from 32.4 MPa for the 5% jute and 25% banana stem leaves (5J25BSL) composite to 40.4 MPa for the 20% jute and 10% banana stem leaves (20J10BSL) composite. Similarly, the flexural strength saw a 27.9% improvement, increasing from 67.2 MPa in the 5J25BSL composite to 86.0 MPa in the 20J10BSL composite. The impact strength also experienced a notable increase of 39.1%, moving from 2.56 J for the 5J25BSL composite to 3.56 J for the 20J10BSL composite. These results highlight significant improvements in all three properties, as the proportion of jute in the composite increased and the proportion of banana stem leaves decreased. This research influences material selection for engineering applications and informs the development of specialized composite materials.